A double-crosslinked in-situ synthesized selenium nanohydrogel, and a preparation method and application thereof
Patent Information
- Application Number
- CN202611280664.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-23
- Publication Date
- 2026-10-13
AI Technical Summary
[0004]虽然蛋白纳米硒凝胶具有良好的抗氧化、抑菌等效果,但是同一些化学合成的纳米硒存在同一个问题,无法保证完全地均匀分散在水凝胶中,容易造成团聚现象;在释放过程中,容易在高蛋白酶富集区集中释放,造成局部纳米硒含量过高的情况;且蛋白纳米硒凝胶的制作过程较为繁琐,需要先对蛋白进行改性再来还原纳米硒,对于实验设备和操作技术的要求较高
[0023](1)本发明采用物理共混法,巧妙地将明胶与其它生物相容性材料结合,设计了一种新型双交联原位合成纳米硒水凝胶敷料,旨在为普通创面治疗提供更有效的方案。
Smart Images

Figure CN122894545A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to a nano-selenium hydrogel, its preparation method and application, specifically to a double-crosslinked in-situ synthesized nano-selenium hydrogel, its preparation method and application, belonging to the field of biomedical materials technology. Background Technology
[0002] The skin is the body's largest physical barrier. When damaged, its natural protective mechanisms fail, allowing microorganisms to easily invade and multiply at the wound site, leading to severe wound infections. Bacterial wound infections can hinder the normal healing process and, in severe cases, cause immune dysfunction and endanger life. Hydrogel dressings possess excellent moisturizing, exudate absorption, and physical isolation properties, effectively protecting damaged wounds and making them an ideal dressing choice for wound repair. However, ordinary hydrogel dressings only provide moisturizing and physical isolation; they lack antibacterial and anti-inflammatory effects. While effective for chronic, slow-healing wounds, they can even create a breeding ground for bacteria due to the moist environment, increasing the risk of secondary infection.
[0003] Existing technology CN120437168A discloses the use of protein-based selenium nanogels in the preparation of wound repair and scar prevention drugs. Albumin (such as human serum albumin) is treated with a reducing agent under specific conditions, then reacted with a selenium-containing compound to obtain protein-based selenium nanoparticles. These nanoparticles are then uniformly dispersed in a hydrogel matrix (such as carbomer gel). This protein-based selenium nanogel exhibits better stability and stronger antioxidant, antibacterial, and anti-inflammatory effects than nano-selenium gels prepared by traditional methods. It demonstrates superior functionality in repairing wounds and inhibiting scar formation in diabetic wounds, making it well-suited for the preparation of wound repair and scar prevention drugs.
[0004] Although protein nano-selenium gels have good antioxidant and antibacterial effects, they share the same problem as some chemically synthesized nano-selenium: they cannot be guaranteed to be completely and uniformly dispersed in the hydrogel, which easily leads to aggregation. During the release process, they tend to be concentrated in areas with high protease enrichment, resulting in excessively high local nano-selenium content. Moreover, the preparation process of protein nano-selenium gels is relatively complicated, requiring modification of the protein before reducing the nano-selenium, which places high demands on experimental equipment and operating techniques.
[0005] Therefore, it is imperative to develop a gel capable of in-situ reduction of selenium nanoparticles, easy to manipulate, and capable of uniform and slow release. Gelatin is a denatured fibrous protein made from collagen, rich in numerous bioactive sequences, such as the arginine-glycine cell-binding site, which facilitates cell adhesion and spreading, exhibiting good biocompatibility. Furthermore, the gelatin molecular chain, containing a large number of amino acid residues, is easily chemically modified, demonstrating good maneuverability. This invention utilizes this characteristic, reacting methacrylic anhydride with the amino groups in gelatin to obtain methacrylated gel (GelMA), which can form a hydrogel through photo-initiated free radical polymerization, endowing it with better cross-linking ability, improved mechanical properties, and good biocompatibility. Summary of the Invention
[0006] The technical problem to be solved by this invention is to address the shortcomings of existing technologies by providing a double-crosslinked in-situ synthesized nano-selenium hydrogel, its preparation method, and its application. Compared with protein nano-selenium gel, the nano-selenium hydrogel prepared by this invention not only has the advantages of excellent broad-spectrum antibacterial properties and tissue healing promotion, as well as excellent anti-inflammatory and antioxidant capabilities, but can also clear ROS around wounds and promote the transformation of macrophages from the pro-inflammatory phase to the anti-inflammatory phase. In addition, the nano-selenium hydrogel of this invention can synthesize nano-selenium in situ during the ion crosslinking process, uniformly dispersing nano-selenium inside the hydrogel, giving it better crosslinking ability and better mechanical properties, and good biocompatibility.
[0007] To achieve the above objectives, the present invention adopts the following technical solution:
[0008] One objective of this invention is to provide a method for preparing double-crosslinked in-situ synthesized nano-selenium hydrogels, comprising the following steps:
[0009] (1) Preparation of methacrylamide gelatin:
[0010] Gelatin was added to PBS solution and stirred at 40-60℃ to fully dissolve it and form a gelatin solution. The pH of the gelatin solution was adjusted to 8-9, and methacrylic anhydride was slowly added under water bath conditions at 40-60℃ to carry out the reaction. After the reaction was completed, PBS solution was added to the reaction solution to terminate the reaction. The system was then dialyzed and freeze-dried to obtain a white spongy product, methacrylamide gelatin.
[0011] (2) Preparation of sodium alginate oxide:
[0012] Sodium alginate was added to a PBS solution with a pH of 5±0.1 and stirred until it was fully dissolved to form a sodium alginate solution. Sodium periodate was added to the sodium alginate solution to carry out the reaction. After the reaction was completed, ethylene glycol was added to the reaction solution to terminate the reaction. The system was then subjected to dialysis and freeze-drying to obtain a white spongy product, sodium oxidized alginate.
[0013] (3) Preparation of GelMA-OSA-SeNP composite hydrogel:
[0014] The methacrylated gelatin obtained in step (1) and the sodium alginate obtained in step (2) are mixed evenly. Then, calcium ascorbate (VcCa) and sodium selenite are added to the system and stirred evenly. Finally, LAP is added, and a cross-linking reaction is carried out under ultraviolet light irradiation to form a methacrylated gelatin-sodium alginate-calcium ascorbate composite hydrogel, namely GelMA-OSA-SeNP composite hydrogel. The GelMA-OSA-SeNP composite hydrogel is a double cross-linked in-situ synthesized nano-selenium hydrogel.
[0015] In the above technical solution, in step (1), the concentration of gelatin solute in the gelatin solution is 10%-30% (w / v); after slowly adding 0.5-1 times (preferably 0.8) of methacrylic anhydride by weight of gelatin, the reaction is carried out in the dark for 2-4 hours (preferably 3 hours); after the reaction is completed, 4-6 times (preferably 5 times) of PBS solution is added to the reaction solution and stirred for half an hour to terminate the reaction.
[0016] In the above technical solution, in step (1), the system after the reaction is terminated is transferred to a dialysis bag with an 8-14 kDa capacity and dialyzed with deionized water for 5-7 days, with frequent water changes every day to remove unreacted anhydrides and byproducts; after dialysis, the dialyzed solution is freeze-dried for 24-72 h (preferably 48 h) to obtain a white sponge-like product, methacrylamide gelatin.
[0017] In the above technical solution, in step (2), the concentration of sodium alginate in the sodium alginate solution is 1%-3% (w / v); after adding sodium periodate at 1-2 times (preferably 1.5 times) the mass of sodium alginate, the reaction is carried out at room temperature in the dark for 4-6 hours (preferably 5 hours). After the reaction is completed, a small amount of ethylene glycol is added and the mixture is stirred for 0.5-1.5 hours (preferably 1 hour) to terminate the reaction.
[0018] In the above technical solution, in step (2), the system after the reaction is terminated is transferred to an 8-14 KDa dialysis bag and dialyzed with deionized water for about 5-7 days. The water is changed frequently every day to remove unreacted acid anhydrides and byproducts. Finally, the dialyzed solution is freeze-dried for 24-72 h (preferably 48 h) to obtain a white spongy product, sodium oxidized alginate.
[0019] In the above technical solution, in step (3), the mass ratio of the methacrylamide gelatin and sodium alginate oxide is 4-8:1-3 (preferably 5:2); the amount of calcium ascorbate (VcCa) added is 2%-3% of the total mass of the methacrylamide gelatin and sodium alginate oxide; the concentration of sodium selenite in the system is controlled to be 0.01-0.08 mol / L (preferably 0.04 mol / L) after the addition of sodium selenite; the amount of LAP added is 0.1%-0.2% (preferably 0.15%) of the total mass of the methacrylamide gelatin and sodium alginate oxide; the crosslinking reaction under ultraviolet lamp irradiation conditions refers to ultraviolet crosslinking for 1-3 minutes under ultraviolet lamp irradiation with an intensity of 405 nm.
[0020] The second objective of this invention is to provide a double cross-linked in-situ synthesized nano-selenium hydrogel obtained by the above preparation method. The hydrogel is a methacrylated gelatin-oxidized sodium alginate-calcium ascorbate composite hydrogel, namely GelMA-OSA-SeNP composite hydrogel, abbreviated as GOS hydrogel.
[0021] The third objective of this invention is to provide an application of the aforementioned double-crosslinked in-situ synthesized nano-selenium hydrogel in the preparation of dressings that inhibit wound infection and promote wound healing; the aforementioned GOS hydrogel has excellent antioxidant, antibacterial and anti-inflammatory properties, and can effectively inhibit wound infection and promote wound healing.
[0022] Compared with existing technologies, it has the following beneficial effects:
[0023] (1) This invention uses a physical blending method to cleverly combine gelatin with other biocompatible materials to design a novel double cross-linked in-situ synthesized nano-selenium hydrogel dressing, which aims to provide a more effective solution for the treatment of common wounds.
[0024] (2) This invention chemically modifies gelatin to synthesize methacrylamide gelatin (GelMA), endowing gelatin with photocrosslinking ability, thereby enabling it to form a stable three-dimensional network structure through ultraviolet light-induced polymerization. This invention mixes GelMA with sodium oxidized alginate (OSA) and calcium ascorbate (VcCa) to improve the mechanical properties of the hydrogel. This invention uses methacrylamide gelatin / sodium oxidized alginate / calcium ascorbate (GelMA-OSA-SeNP) as the base gel and mixes it with sodium selenite to synthesize nano-selenium in situ during ionic crosslinking of the hydrogel, resulting in a composite hydrogel GelMA-OSA-SeNP (abbreviated as GOS) with antibacterial, anti-inflammatory and antioxidant functions. Attached Figure Description
[0025] Figure 1 The infrared spectra of the composite hydrogel and related products of this invention are shown below, wherein: Figure 1 a represents the infrared spectra of SA and OSA prepared in Example 1; Figure 1 b shows the infrared spectra of the GelMA-OSA-SeNP gel, GelMA, OSA prepared in Example 1, and the GelMA-OSA gel prepared in Comparative Example 1. Figure 1 c represents the infrared spectra of Gel and GelMA prepared in Example 1;
[0026] Figure 2 The images show the 1H NMR spectra of the GelMA and OSA products prepared in Example 1 of this invention. Figure 2 a represents the hydrogen NMR spectra of GelMA and Gel. Figure 2 b shows the 1H NMR spectra of OSA and SA;
[0027] Figure 3 The image shows the nano-selenium release curve of the GelMA-OSA-SeNP composite hydrogel in Example 1 of this invention; where ● represents 0.01 GelMA-OSA-SeNP, ■ represents 0.02 GelMA-OSA-SeNP, ▲ represents 0.04 GelMA-OSA-SeNP, and ▼ represents 0.08 GelMA-OSA-SeNP.
[0028] Figure 4 This is a graph showing the scavenging rates of different gel products against ABTS and DPPH free radicals in the verification examples of this invention; wherein: Figure 4 a shows the scavenging rate of ABTS free radicals after treatment with different gel products for 6 minutes. Figure 4 b is a graph showing the scavenging rate of DPPH free radicals after treatment with different gel products for different times (different capital letters under the numbers on the vertical axis of the bar graph represent different groups, where: A represents DPPH, B represents GelMA, C represents GelMA-OSA, and D represents 0.04GelMA-OSA-SeNP).
[0029] Figure 5 Images showing the antibacterial activity of different gel products against different bacteria in verification embodiments of the present invention;
[0030] Figure 6 In the verification examples of this invention, the antibacterial rates of different gel products against different bacteria were tested; wherein: Figure 6 a represents the inhibition rate of different gel products against E. coli; Figure 6 b represents the inhibition rate of different gel products against S. aureus;
[0031] Figure 7 These are staining images of live and dead cells from L929 mouse fibroblasts co-cultured with different hydrogel products for 1, 2, and 4 days, as part of the verification examples of this invention.
[0032] Figure 8 To verify the cell viability of L929 mouse fibroblasts co-cultured with different hydrogel products for 1, 2, and 4 days in the embodiments of this invention, the different uppercase letters under the numbers on the vertical axis of the bar chart represent different groups, where: A represents Control, B represents GelMA, C represents GelMA-OSA, D represents 0.01GelMA-OSA-SeNP, E represents 0.02GelMA-OSA-SeNP, F represents 0.04GelMA-OSA-SeNP, and G represents 0.08GelMA-OSA-SeNP;
[0033] Figure 9 To verify the cell viability of Raw264.7 mouse macrophages co-cultured with different hydrogel products for 24 hours in this embodiment of the invention;
[0034] Figure 10 This is a graph showing the levels of NaNO2, IL-6, and TNF-α in Raw264.7 mouse macrophages after co-culturing with different hydrogel products for 24 hours in a verification embodiment of the present invention; wherein: Figure 10 a is a diagram showing NaNO2 content. Figure 10 b is the IL-6 content graph. Figure 10 c is a graph showing the content of TNF-α;
[0035] Figure 11 Images shown in this embodiment of the invention are used to detect the healing of mouse wounds after treatment with different gel products.
[0036] Figure 12 This is a model diagram used in the verification embodiment of the present invention to detect the healing of mouse wounds after treatment with different gel products.
[0037] Figure 13 HE staining images are used to detect the healing of mouse wounds after treatment with different gel products in the verification embodiment of the present invention. Detailed Implementation
[0038] The following describes in detail the specific embodiments of the technical solution of the present invention, but the present invention is not limited to the following description:
[0039] Example 1:
[0040] A double-crosslinked in-situ synthesized nano-selenium hydrogel (GelMA-OSA-SeNP composite hydrogel) was prepared by the following method:
[0041] (1) Preparation of methacrylamide gelatin:
[0042] Weigh 1 g of gelatin and add it to 10 mL of PBS solution. Stir at 50°C until fully dissolved to form a 10% gelatin solution. Adjust the pH of the gelatin solution to 8-9, and slowly add 0.8 times the weight of methacrylic anhydride to the solution in a 50°C water bath. React in the dark for 3 hours. After the reaction is complete, add 5 times the volume of PBS and stir for half an hour to terminate the reaction. Transfer the reaction solution to a 10 kDa dialysis bag and dialyze with deionized water for about 6 days, changing the water frequently each day to remove unreacted anhydride and byproducts. Finally, freeze-dry the dialyzed solution for 48 hours to obtain a white, spongy product, methacrylamide gelatin. Infrared images of methacrylamide gelatin (GelMA) and gelatin gelatin are shown below. Figure 1 As shown in c, the 1H NMR spectrum Figure 2 As shown in figure a, this indicates that GelMA was successfully prepared.
[0043] (2) Preparation of sodium alginate oxide:
[0044] Weigh 1g of sodium alginate and add it to 100ml of pH 5 PBS solution. Stir until fully dissolved to form a 1% sodium alginate solution. Add 1.5 times the mass of sodium periodate to the solution and react at room temperature in the dark for 5 hours. After the reaction is complete, add 10ml of ethylene glycol and stir for 1 hour to terminate the reaction. Transfer the reaction solution to a 10 kDa dialysis bag and dialyze with deionized water for about 6 days, changing the water frequently each day to remove unreacted anhydrides and byproducts. Finally, freeze-dry the dialyzed solution for 48 hours to obtain a white, spongy product, oxidized sodium alginate (OSA). Infrared images of oxidized sodium alginate (OSA) and sodium alginate (SA) are shown below. Figure 1 As shown in a, the 1H NMR spectrum Figure 2 As shown in b, this indicates that OSA preparation was successful.
[0045] (3) Preparation of GelMA-OSA-SeNP composite hydrogel
[0046] Methacrylamide gelatin and sodium alginate were mixed evenly at a mass ratio of 5:2. Then, 2.5% calcium ascorbate (VcCa) and 0.04 mol / L sodium selenite were added and stirred until homogeneous. Next, 0.15% LAP was added, and the mixture was UV cross-linked under a 405 nm UV lamp for 2 minutes to form a hydrogel. The resulting hydrogel is the GelMA-OSA-SeNP composite hydrogel. The infrared image of the GelMA-OSA-SeNP composite hydrogel is shown below. Figure 1 As shown in b, this demonstrates the successful preparation of the GelMA-OSA-SeNP composite hydrogel of the present invention.
[0047] Comparative Example 1:
[0048] A GelMA-OSA composite hydrogel was prepared by the following method:
[0049] (1) Preparation of methacrylamide gelatin:
[0050] Weigh 1g of gelatin and add it to 10mL of PBS solution. Stir at 50℃ until fully dissolved to form a 10% gelatin solution. Adjust the pH of the gelatin solution to 8-9, and slowly add 0.8 times the weight of methacrylic anhydride to the solution in a 50℃ water bath. React in the dark for 3 hours. After the reaction is complete, add 5 times the volume of PBS and stir for half an hour to terminate the reaction. Transfer the reaction solution to a 10 kDa dialysis bag and dialyze with deionized water for about 6 days, changing the water frequently each day to remove unreacted anhydride and byproducts. Finally, freeze-dry the dialyzed solution for 48 hours to obtain a white, spongy product, methacrylamide gelatin.
[0051] (2) Preparation of sodium alginate oxide:
[0052] Weigh 1g of sodium alginate and add it to 100ml of pH 5 PBS solution. Stir until fully dissolved to form a 1% sodium alginate solution. Add 1.5 times the mass of sodium periodate to the sodium alginate solution and react at room temperature in the dark for 5 hours. After the reaction is complete, add 10ml of ethylene glycol and stir for 1 hour to terminate the reaction. Transfer the reaction solution to a 10 kDa dialysis bag and dialyze with deionized water for about 6 days, changing the water frequently every day to remove unreacted anhydrides and byproducts. Finally, freeze-dry the dialyzed solution for 48 hours to obtain a white, spongy product, oxidized sodium alginate.
[0053] (3) Preparation of GelMA-OSA composite hydrogel:
[0054] Methacrylamide gelatin and sodium alginate were mixed evenly at a mass ratio of 5:2. 0.15% LAP was added, and the mixture was UV cross-linked for 2 minutes under a 405 nm UV lamp to form a hydrogel. The resulting hydrogel is the GelMA-OSA composite hydrogel. The infrared image of the GelMA-OSA composite hydrogel is shown below. Figure 1 As shown in b.
[0055] Comparative Example 2:
[0056] A GelMA hydrogel was prepared by the following method:
[0057] (1) Preparation of methacrylamide gelatin:
[0058] Weigh 1 g of gelatin and add it to 10 mL of PBS solution. Stir at 50°C until fully dissolved to form a 10% gelatin solution. Adjust the pH of the gelatin solution to 8-9, and slowly add 0.8 times the weight of methacrylic anhydride to the solution in a 50°C water bath. React in the dark for 3 hours. After the reaction is complete, add 5 times the volume of PBS and stir for half an hour to terminate the reaction. Transfer the reaction solution to a 10 kDa dialysis bag and dialyze with deionized water for about 6 days, changing the water frequently each day to remove unreacted anhydride and byproducts. Finally, freeze-dry the dialyzed solution for 48 hours to obtain a white, spongy product, methacrylamide gelatin.
[0059] (2) Prepare a 10% solution of the above methacrylamide gelatin, add 0.15% LAP, and crosslink with a UV lamp with an intensity of 405 nm for 2 min to form a hydrogel. The hydrogel obtained is GelMA hydrogel.
[0060] Verification Example:
[0061] 1. Verify the selenium release curves of hydrogel products with different selenium contents:
[0062] The selenium content in the prepared GelMA-OSA-SeNP hydrogels was controlled by adding sodium selenite at concentrations of 0.01 mol / L, 0.02 mol / L, 0.04 mol / L, and 0.08 mol / L in step (3) of Example 1, respectively. The resulting hydrogel products were named 0.01GelMA-OSA-SeNP, 0.02GelMA-OSA-SeNP, 0.04GelMA-OSA-SeNP (i.e., the product in Example 1), and 0.08GelMA-OSA-SeNP, respectively. The same mass (0.6 g) of each hydrogel with different selenium contents was placed in 50 ml of PBS and cultured in a shaker at 37°C. At different time points, 3 ml of the solution was taken, and 3 ml of fresh PBS was added. The solution was then acidified using 1 ml of pure nitric acid and 300 μl of 30% hydrogen peroxide. After acid removal at 130°C for 45 min, the solution was diluted to 50 ml with pure water. 10 ml of the sample was taken and the release of SeNPs was detected using ICP-OES. The release curve is shown below. Figure 3 As shown, by Figure 3 It can be seen that the hydrogel with a selenium content of 0.01 mol / L can ultimately release 11.4324 mg / L of nano-selenium, the hydrogel with a selenium content of 0.02 mol / L can ultimately release 22.596 mg / L of nano-selenium, the hydrogel with a selenium content of 0.04 mol / L can ultimately release 41.7292 mg / L of nano-selenium, and the hydrogel with a selenium content of 0.08 mol / L can ultimately release 71.5693 mg / L of nano-selenium. Considering all the experimental results, adding 0.04 mol / L of selenium during the preparation of hydrogels is the most appropriate release amount.
[0063] 2. Verify the effect of different gel products on the scavenging effects of ABTS and DPPH free radicals:
[0064] DPPH was dissolved in anhydrous ethanol at a concentration of 0.1 mM. 10 mg of different hydrogel samples were added to 3 mL of DPPH solution and incubated at room temperature in the dark for 30 min, 2 h, and 24 h, respectively. Pure DPPH solution served as a blank control. Then, 100 μL of each sample was added to a 96-well plate, and the absorbance of the supernatant at 517 nm was measured using a microplate reader. The DPPH radical scavenging rate under the time gradient was calculated.
[0065] Prepare 7 mmol / L ABTS reagent and 2.25 mmol / L potassium persulfate solution. Mix equal volumes of the two solutions in the dark at room temperature and react for 12–16 h to generate ABTS stock solution. Dilute the stock solution approximately 50 times with deionized water until the absorbance at 734 nm reaches 0.7 ± 0.02, thus obtaining the ABTS working solution. Add 3 ml of ABTS working solution to 10 mg of different hydrogel samples and react in the dark for 6 min. Use an equal volume of deionized water as a blank control. Take 100 μL of the mixture into a 96-well plate and measure the absorbance at 734 nm using a microplate reader. Calculate the ABTS free radical scavenging rate after 6 min.
[0066] The scavenging effects of the GelMA-OSA-SeNP hydrogel obtained in Example 1 (i.e., 0.04 GelMA-OSA-SeNP prepared by adding 0.04 mol / L sodium selenite), the GelMA-OSA hydrogel obtained in the comparative example, and the GelMA hydrogel on ABTS and DPPH free radicals are as follows: Figure 4 As shown: by Figure 4 It can be seen that the GelMA-OSA-SeNP hydrogel prepared by the present invention has a significantly better scavenging effect on ABTS free radicals and DPPH free radicals than GelMA-OSA hydrogel and GelMA hydrogel, indicating that the GelMA-OSA-SeNP hydrogel of the present invention has excellent antioxidant effect.
[0067] 3. Verify the effect of different gel products on the inhibitory effects of Staphylococcus aureus and Escherichia coli:
[0068] The plate count method was used to investigate the inhibitory effects of 0.01 GelMA-OSA-SeNP hydrogels, 0.02 GelMA-OSA-SeNP hydrogels, 0.04 GelMA-OSA-SeNP hydrogels (i.e., the product in Example 1), 0.08 GelMA-OSA-SeNP hydrogels, and the comparative GelMA-OSA hydrogels prepared with different amounts of sodium selenite on Staphylococcus aureus and Escherichia coli.
[0069] Inhibitory effects against Staphylococcus aureus and Escherichia coli were as follows: Figure 5 and Figure 6 As shown, the GelMA-OSA-SeNP hydrogel prepared by adding 0.01-0.08 mol / L sodium selenite exhibits extremely significant inhibitory effects on Staphylococcus aureus and Escherichia coli, with inhibition rates significantly higher than those of GelMA-OSA hydrogel. This indicates that the GelMA-OSA-SeNP hydrogel of the present invention has excellent antibacterial effects. Considering the cost of raw materials, adding 0.04 mol / L sodium selenite yields the best results.
[0070] 4. Verify the effect of different gel products on the survival of L929 mouse fibroblasts:
[0071] Hydrogels of 0.01 GelMA-OSA-SeNP, 0.02 GelMA-OSA-SeNP, 0.04 GelMA-OSA-SeNP (i.e., the product in Example 1), 0.08 GelMA-OSA-SeNP, and the comparative GelMA hydrogel were prepared by adding different amounts of sodium selenite at a ratio of 0.1 g / ml. The GelMA hydrogels were immersed in DMEM high-glucose medium and cultured in a shaker at 37°C for 24 h. The effect of the hydrogel extract on the survival of L929 mouse fibroblasts was then detected.
[0072] Images of live and dead cells stained after 1, 2, and 4 days of co-culturing L929 mouse fibroblasts with different hydrogel products were obtained from [the image description]. Figure 7 As shown, the cell viability of L929 mouse fibroblasts co-cultured with different hydrogel products for 1, 2, and 4 days increased from [previous data]. Figure 8 As shown; by Figure 7 and Figure 8It can be seen that when L929 mouse fibroblasts were co-cultured with the GelMA-OSA-SeNP hydrogel product prepared by adding 0.01-0.04 mol / L sodium selenite for 24-96 hours, the cell survival rate reached more than 80%, indicating that the GelMA-OSA-SeNP hydrogel product prepared by this invention has no cytotoxicity and good biocompatibility.
[0073] 5. Verify the effects of different gel products on the survival and anti-inflammatory properties of macrophages in Raw264.7 mice:
[0074] Hydrogels of 0.01 GelMA-OSA-SeNP, 0.02 GelMA-OSA-SeNP, 0.04 GelMA-OSA-SeNP (i.e., the product in Example 1), 0.08 GelMA-OSA-SeNP, and the comparative GelMA hydrogel were prepared by adding different amounts of sodium selenite at a ratio of 0.1 g / ml. These hydrogels were then immersed in DMEM high-glucose medium and cultured in a shaker at 37°C for 24 h. The effect of the hydrogel extract on the survival of Raw264.7 mouse macrophages was then examined. The results are as follows: Figure 9 As shown, after adding 0.01-0.04 mol / L sodium selenite to prepare the GelMA-OSA-SeNP hydrogel product, and co-culturing it with macrophages for 24 h, the cell survival rate was not significantly different from the control group, reaching over 90%. This indicates that the GelMA-OSA-SeNP hydrogel product does not significantly cause macrophage necrosis / apoptosis and has no direct acute toxicity to macrophages.
[0075] Hydrogels containing different amounts of sodium selenite (0.1 g / ml) were prepared, resulting in 0.01 GelMA-OSA-SeNP hydrogels, 0.02 GelMA-OSA-SeNP hydrogels, 0.04 GelMA-OSA-SeNP hydrogels (i.e., the product in Example 1), 0.08 GelMA-OSA-SeNP hydrogels, and a comparative GelMA hydrogel. These hydrogels were immersed in DMEM high-glucose medium and cultured at 37°C in a shaker for 24 h. The effects of the hydrogel extract on the levels of NaNO2, IL-6, and TNF-α after co-culturing LPS-induced Raw264.7 mouse macrophages for 24 hours were detected using a NO reagent detection kit and an ELISA kit. The results are as follows: Figure 10 As shown, the GelMA-OSA-SeNP hydrogel product prepared by adding 0.01-0.04 mol / L sodium selenite and co-culturing it with macrophages for 24 days significantly reduced the release of NO, IL-6, and TNF-α compared with the LPS negative control group, indicating that the GelMA-OSA-SeNP hydrogel of the present invention has excellent anti-inflammatory effects.
[0076] 6. Verify the effects of different gel products on wound healing in mice:
[0077] The effects of the GelMA-OSA-SeNP hydrogel obtained in Example 1, the GelMA-OSA hydrogel obtained in Comparative Example 1, and the GelMA hydrogel obtained in Comparative Example 2 on wound healing were examined.
[0078] A circular wound with a diameter of 8 mm was created on the skin of the mouse's back. Sterilized GelMA-OSA-SeNP hydrogel, GelMA-OSA hydrogel, and GelMA hydrogel were applied to the wound, respectively. After 2 minutes of UV irradiation, the wound was secured with a bandage and kept clean. The wound was observed regularly, and cleaned with saline solution and cotton swabs. The hydrogel dressing was changed every 2 days. The control group received no treatment. Images were taken on days 0, 6, 12, and 18, and the wound healing process was analyzed using ImageJ.
[0079] Mice were harvested on days 6, 12, and 18. Wound tissue was washed with physiological saline and then fixed with 4% paraformaldehyde for 24 hours. The fixed tissue was then embedded in paraffin and serial 5μm sections were obtained using a microtome. To assess wound healing, hematoxylin and eosin (H&E) assays were used to observe inflammatory responses and cell proliferation at the wound site.
[0080] The healing results are as follows Figure 11 and Figure 12 As shown in Table 1, the wound healing rate was as follows. Compared with the control group, the wounds treated with GelMA-OSA-SeNP hydrogel had scabs formed by day 6 and the area had decreased. By day 12, the wounds were basically healed and the scabs showed signs of falling off. By day 18, the wounds were completely healed. Hair growth around the wounds was vigorous and close to that of the surrounding healthy skin. This demonstrates that GelMA-OSA-SeNP hydrogel is a hydrogel material that can specifically treat skin wounds and can promote wound healing in mice to a certain extent.
[0081] The inflammation and cell proliferation status of the wound, such as Figure 13 As shown, on day 6 post-treatment, compared to the control group, the GelMA-OSA-SeNP hydrogel treatment group exhibited neater scab formation, denser subcutaneous cells, milder inflammation, and better wound healing. On day 12, compared to the control group, the GelMA-OSA-SeNP hydrogel treatment group showed the best wound closure and new epidermis growth. After 18 days of treatment, compared to other groups, the GelMA-OSA-SeNP group had formed a complete epidermis with the appearance of hair follicles, demonstrating that the wound healing potential of GelMA-OSA-SeNP hydrogel is superior to other groups.
[0082] Based on the results of the above experiments, the results of the GelMA-OSA-SeNP hydrogel obtained in Example 1, the GelMA-OSA hydrogel obtained in Comparative Example 1, and the GelMA hydrogel obtained in Comparative Example 2 on DPPH free radical scavenging rate, ABTS free radical scavenging rate, E. coli antibacterial rate, S. aur. antibacterial rate, and wound healing rate were summarized, and the results are shown in Figure 1:
[0083] Table 1: Product Performance of Different Hydrogel Products
[0084]
[0085] As can be seen from the above results, the GelMA-OSA-SeNP described in this invention has excellent antioxidant, anti-inflammatory and antibacterial effects, good cell compatibility, and also has a certain effect on promoting wound healing in mice.
[0086] The above examples are merely illustrative of the technical concept and features of the present invention and should not be construed as limiting the scope of protection of the present invention. All equivalent transformations or modifications made in accordance with the essence of the present invention should be included within the scope of protection of the present invention.
Claims
1. A method for preparing a double-crosslinked in-situ synthesized nano-selenium hydrogel, characterized in that, Includes the following steps: (1) Preparation of methacrylamide gelatin: Gelatin was added to PBS solution and stirred at 40-60℃ to fully dissolve it and form a gelatin solution. The pH of the gelatin solution was adjusted to 8-9, and methacrylic anhydride was slowly added under water bath conditions at 40-60℃ to carry out the reaction. After the reaction was completed, PBS solution was added to the reaction solution to terminate the reaction. The system was then dialyzed and freeze-dried to obtain a white spongy product, methacrylamide gelatin. (2) Preparation of sodium alginate oxide: Sodium alginate was added to a PBS solution with a pH of 5±0.1 and stirred until it was fully dissolved to form a sodium alginate solution. Sodium periodate was added to the sodium alginate solution to carry out the reaction. After the reaction was completed, ethylene glycol was added to the reaction solution to terminate the reaction. The system was then subjected to dialysis and freeze-drying to obtain a white spongy product, sodium oxidized alginate. (3) Preparation of GelMA-OSA-SeNP composite hydrogel: The methacrylated gelatin obtained in step (1) and the sodium alginate obtained in step (2) are mixed evenly. Then, calcium ascorbate (VcCa) and sodium selenite are added to the system and stirred evenly. Finally, LAP is added, and a cross-linking reaction is carried out under ultraviolet light irradiation to form a methacrylated gelatin-sodium alginate-calcium ascorbate composite hydrogel, namely GelMA-OSA-SeNP composite hydrogel. The GelMA-OSA-SeNP composite hydrogel is a double cross-linked in-situ synthesized nano-selenium hydrogel.
2. The preparation method according to claim 1, characterized in that, In step (1), the concentration of gelatin solute in the gelatin solution is 10%-30% (w / v); after slowly adding 0.5-1 times the mass of gelatin in methacrylic anhydride, the reaction is carried out in the dark for 2-4 hours; after the reaction is completed, 4-6 times the volume of PBS solution is added to the reaction solution and stirred for half an hour to terminate the reaction.
3. The preparation method according to claim 1, characterized in that, In step (1), the system after the reaction is terminated is transferred to an 8-14 kDa dialysis bag and dialyzed with deionized water for 5-7 days, with frequent water changes every day to remove unreacted anhydrides and byproducts; after dialysis, the dialyzed solution is freeze-dried for 24-72 h to obtain a white sponge-like product, methacrylamide gelatin.
4. The preparation method according to claim 1, characterized in that, In step (2), the sodium alginate solution has a concentration of 1%-3% (w / v) of sodium alginate. After adding sodium periodate at a mass of 1-2 times that of sodium alginate, the reaction is carried out at room temperature in the dark for 4-6 hours. After the reaction is completed, a small amount of ethylene glycol is added and the mixture is stirred for 0.5-1.5 hours to terminate the reaction.
5. The preparation method according to claim 1, characterized in that, In step (2), the system after the reaction is terminated is transferred to an 8-14 kDa dialysis bag and dialyzed with deionized water for about 5-7 days, with frequent water changes every day to remove unreacted anhydrides and byproducts. Finally, the dialyzed solution is freeze-dried for 24-72 h to obtain a white sponge-like product, sodium oxidized alginate.
6. The preparation method according to claim 1, characterized in that, In step (3), the mass ratio of methacrylamide gelatin and sodium alginate oxide is 4-8:1-3; the amount of calcium ascorbate added is 2%-3% of the total mass of methacrylamide gelatin and sodium alginate oxide; the concentration of sodium selenite in the system is controlled to be 0.01-0.08 mol / L after addition; the amount of LAP added is 0.1%-0.2% of the total mass of methacrylamide gelatin and sodium alginate oxide; the crosslinking reaction under ultraviolet light irradiation refers to ultraviolet crosslinking for 1-3 minutes under ultraviolet light irradiation with an intensity of 405 nm.
7. A double-crosslinked in-situ synthesized nano-selenium hydrogel prepared by the preparation method according to any one of claims 1-6, characterized in that, The hydrogel is a methacrylated gelatin-oxidized sodium alginate-calcium ascorbate composite hydrogel, namely GelMA-OSA-SeNP composite hydrogel.
8. The application of the double cross-linked in-situ synthesized nano-selenium hydrogel according to claim 7 in the preparation of dressings that inhibit wound infection and promote wound healing.
Citation Information
Patent Citations
Application of protein nano-selenium hydrogel in preparation of drugs for wound repair and scar prevention and treatment
CN120437168A